# Thread: Inverse of Linear Function

1. ## Inverse of Linear Function

If f is a linear function such that f(x+2)-f(x)=6
find the value of f^-1(x+2)-f^-1(x)

2. Originally Posted by vvc531
If f is a linear function such that f(x+2)-f(x)=6
find the value of f^-1(x+2)-f^-1(x)
hi

let the function be ax+b

f(x+2)-f(x)=6

ax+2a+b-ax-b=6

2a=6 , a=3

so f(x)=3x-b

Now , find their inverses ,

$\displaystyle f^{-1}(x)=\frac{x-b}{3}$

$\displaystyle f^{-1}(x+2)=\frac{x+2-b}{3}$

then do as the question asks .

I have already done the steps shown. Can someone show me the answer so I can verity whether mine is correct?

4. Originally Posted by vvc531
I have already done the steps shown. Can someone show me the answer so I can verity whether mine is correct?
If you had said this in the first place then:

1. You would have got the help you needed a lot faster.

2. People wouldn't be wasting their time - unpaid - posting things you have already done.

If you want verification of an answer, say what answer you got.